2021
DOI: 10.3390/fermentation7010031
|View full text |Cite
|
Sign up to set email alerts
|

Application of Autochthonous Yeast Saccharomyces cerevisiae XG3 in Treixadura Wines from D.O. Ribeiro (NW Spain): Effect on Wine Aroma

Abstract: Yeast plays an essential role in winemaking. Saccharomyces cerevisiae strains involved in fermentation determine the chemical and sensory characteristics of wines. S. cerevisiae XG3, isolated in Galicia (NW Spain), has desirable oenological potential, which has been proved at a pilot scale to produce quality wines. This study applies XG3 as active dry yeast at an industrial scale for Treixadura wine elaboration, and compares it with commercial yeast and spontaneous fermentation within three wineries included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The use of strains isolated from different Denominations of Origin (DOs) and from different plots and cultivation systems within the same species allowed to explore different oenological behaviours to select the most appropriate ones. In addition, the S. cerevisiae XG3 strain, previously tested and selected at EVEGA, was used as a control [25,26].…”
Section: Origin Of Yeast Strains and Sampling Designmentioning
confidence: 99%
“…The use of strains isolated from different Denominations of Origin (DOs) and from different plots and cultivation systems within the same species allowed to explore different oenological behaviours to select the most appropriate ones. In addition, the S. cerevisiae XG3 strain, previously tested and selected at EVEGA, was used as a control [25,26].…”
Section: Origin Of Yeast Strains and Sampling Designmentioning
confidence: 99%
“…It has been shown that this strain excelled in fermentative vigor and has positive effects on the chemical and sensory characteristics of the wines produced from the white cultivars at the laboratory and pilot scale [9,10]. Here, Blanco et al [11] applied this strain for the production of Treixadura wine at an industrial scale. The Galician Treixadura is one of the main traditional white cultivars that is characterized by fruity and floral descriptors due to high concentrations of ethyl esters and volatile acids [12].…”
Section: Wine Yeasts and Wine Fermentationmentioning
confidence: 99%